Christian humanism in Shakespeare : a study in religion and literature - Oser, Lee, 1958- (The Catholic University of America Press, 2022)
"Oser reviews the rival cases for a Protestant Shakespeare and for a Catholic Shakespeare, but leaves the issue open, focusing, instead, on how Shakespeare exploits artistic resources that are specific to Christianity, including the classical-Christian rhetorical tradition. The scope of the book ranges from an introductory survey of the critical field as it now stands, to individual chapters on A Midsummer Night's Dream, The Merchant of Venice, the Henriad, Hamlet, and King Lear. Oser holds that mainstream literary criticism has created a false picture of Shakespeare by secularizing him and misconstruing the nature of his art. Through careful study of the plays, the author portrays Shakespeare as a friend to the enduring project of humanistic education"--